Anti-Apolipoprotein A-1 IgG Predict All-Cause Mortality and Are Associated with Fc Receptor-Like 3 Polymorphisms - Antiochos, Panagiotis; Marques-Vidal, Pedro; Virzi, Julien; Pagano, Sabrina; Satta, Nathalie; Hartley, Oliver; Montecucco, Fabrizio; Mach, François; Kutalik, Zoltán; Waeber, Gerard; Vollenweider, Peter; Vuilleumier, Nicolas (Frontiers in Immunology, 2017)
Background: Autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) have emerged as an independent biomarker for cardiovascular disease and mortality. However, their association with all-cause mortality in the community as well as their possible genetic determinants have not been studied. Objective: To determine whether anti-apoA-1 IgG: a) predict all-cause mortality in the general population, and b) are associated with single–nucleotide polymorphisms (SNPs) in a genome-wide association study (GWAS). Methods: Clinical, biological and genetic data from the population-based, prospective CoLaus study, including 5220 participants (mean age 52.6 years, 47.3% men) followed over a median duration of 5.6 years. The primary study outcome was all-cause mortality. Results: After multivariate adjustment, anti-apoA-1 IgG positivity independently predicted all-cause mortality: hazard ratio (HR)=1.54, 95% Confidence Interval (95%CI): (1.11-2.13), P=0.01. A dose-effect relationship was also observed, each standard deviation of logarithmically transformed anti-apoA-1 IgG being associated with a 15% increase in mortality risk: HR=1.15, 95%CI: (1.02-1.28), P=0.028. The GWAS yielded 9 SNPs belonging to the Fc receptor like-3 (FCRL3) gene that were significantly associated with anti-apoA-1 IgG levels, with the lead SNP (rs6427397, P=1.54×10-9) explaining 0.67% of anti-apoA-1 IgG level variation. Conclusion: Anti-apoA-1 IgG levels a) independently predict all-cause mortality in the general population and b) are linked to FCRL3, a susceptibility gene for numerous autoimmune diseases. Our findings indicate that preclinical autoimmunity to anti-apoA-1 IgG may represent a novel mortality risk factor.